Conduction system pacing vs. biventricular pacing in patients with ventricular dysfunction and AV block. Issue 9 (1st June 2022) - Pujol‐López, Margarida; Jiménez Arjona, Rafael; Guasch, Eduard; Borràs, Roger; Doltra, Adelina; Vázquez‐Calvo, Sara; Roca‐Luque, Ivo; Garre, Paz; Ferró, Elisenda; Niebla, Mireia; Carro, Esther; Puente, Jose L.; et al.
Abstract: Background: It is unknown whether His‐Purkinje conduction system pacing (HPCSP), as either His bundle or left bundle branch pacing, could be an alternative to cardiac resynchronization therapy (BiVCRT) for patients with left ventricular dysfunction needing ventricular pacing due to atrioventricular block. The aim of the study is to compare the echocardiographic response and clinical improvement between HPCSP and BiVCRT. Methods: Consecutive patients who successfully received HPCSP were compared with a historical cohort of BiVCRT patients. Patients were 1:1 matched by age, LVEF, atrial fibrillation, renal function and cardiomyopathy type. Responders were defined as patients who survived, did not require heart transplantation and increased LVEF ≥5 points at 6‐month follow‐up. Results: HPCSP was successfully achieved in 92.5% (25/27) of patients. During follow‐up, 8% (2/25) of HPCSP patients died and 4% (1/25) received a heart transplant, whereas 4% (1/25) of those in the BiVCRT cohort died. LVEF improvement was 10% ± 8% HPCSP versus 7% ± 5% BiVCRT ( p = .24), and the percentage of responders was 76% (19/25) HPCSP versus 64% (16/25) BiVCRT ( p = .33). Among survivors, the percentage of patients who improved from baseline II–IV mitral regurgitation (MR) to 0–I MR was 9/11 (82%) versus 2/8 (25%) ( p = .02). Compared to those with BiVCRT, patients with HPCSP achieved better NYHA improvement: 1 point versus 0.5 (OR 0.34; p = .02). Conclusion: HPCSP in patients with LVEF ≤45% and atrioventricular block improved the LVEF and induced a response similar to that of BiVCRT. HPCSP significantly improved MR and NYHA functional class. HPCSP may be an alternative to BiVCRT in these patients. (Figure 1 . Central Illustration).